URANIUM MARKET TRENDS - Serghei MĂRGULESCU; Elena MĂRGULESCU (Challenges of the Knowledge Society)
The recent UN Climate Talks in Paris have put forward the goal of limiting the global temperature rise to two degrees Celsius by the end of the century. This is providing a strong political base for expanding the nuclear power capacity because of the critical role that nuclear power plants play in the production of electricity without emissions of greenhouse gases. In all, more than a dozen countries get over 25% of their energy from nuclear power, with 437 nuclear reactors operating around the world. On top of that, there are another 71 reactors under construction, 165 planned, and 315 proposed. Global uranium demand is expected to rise 40% by 2025 and 81% by 2035. Mined supply of uranium will struggle to keep pace amid rising demand and falling secondary supplies. A cumulative supply deficit is expected to emerge by 2021 while 2016 marks a huge inflection point for the industry, beeing the first year that demand will actually exceed supplies, creating a 60,000-tonne shortfall by 2018. Over the next 10 years, we're going to see uranium prices more than double while the bull run will begin in earnest in 2016.